2002
DOI: 10.1021/ac025808b
|View full text |Cite
|
Sign up to set email alerts
|

Nanochannels on a Fused-Silica Microchip and Liquid Properties Investigation by Time-Resolved Fluorescence Measurements

Abstract: We have fabricated nanometer-sized channels, demonstrated a technique for the introduction of liquid into the channels, and carried out time-resolved fluorescence measurements of aqueous solutions. In this study, 330-nm- and 850-nm-sized channels were fabricated on fused-silica substrates by fast atom beam etching and hydrofluoric acid bonding methods. A liquid introduction method utilizing capillary action was demonstrated. The liquid introduction was observed under an optical microscope, and the liquid veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
188
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(199 citation statements)
references
References 35 publications
7
188
4
Order By: Relevance
“…This is not in contradiction to our observations, since their channels were only 100 µm long [16], and we only observed a few bubbles for every millimeter after the channels were filled (Fig. 3b).…”
Section: Filling Long Nanochannels With Water and Trapping Aircontrasting
confidence: 53%
See 1 more Smart Citation
“…This is not in contradiction to our observations, since their channels were only 100 µm long [16], and we only observed a few bubbles for every millimeter after the channels were filled (Fig. 3b).…”
Section: Filling Long Nanochannels With Water and Trapping Aircontrasting
confidence: 53%
“…Yang et al reported the marching velocity of capillary menisci in 500-nm-deep silicon nitride channels [18]. Hibara et al reported filling kinetics in 300-nm-deep channels fabricated in fused silica [16]. Both investigated channels of rectangular cross-section and they also observed the l ∼ t 1/2 relation.…”
Section: Washburn Kinetics In Channels With Different Depthmentioning
confidence: 97%
“…The authors consider this indirect proof of the higher viscosity of water in the channel compared to the bulk solution. In other work [23,44] it was found that water in a 300 nm-sized quartz glass nanochannel was a factor of three slower than predicted by the Hagen-Poiseuille law.…”
Section: Transport In Nanochannelsmentioning
confidence: 83%
“…The most sensitive method is fluorescence, although this is not a generally applicable technique because molecules must be labeled in order to be able to use it; this means that the very nature of the molecules to be studied may change such that they are no longer relevant for the chemical problem under study. Fluorescence has proven to be very useful for characterizing the properties of liquids [44], where it is mostly used as a tracer for velocity measurement or zone dispersion. It is essential in studies of DNA behavior and protein folding (in the latter, the fluorescence intensity depends on the folding state).…”
Section: Analysis On Nanochannelsmentioning
confidence: 99%
“…Filling by capillary forces, electroosmotic flow (EOF) and an increased surface to volume ratio are major concerns, which influence the choice of suitable materials for nanochannels and its fabrication technique (Tas et al 2003). Sacrificial layer etching, nanoimprint lithography, e-beam lithography and other methods have already been successfully applied for nanochannel fabrication (Guo et al 2004;Yu et al 2003;Cao et al 2002a, b;Hibara et al 2002;Lee et al 2003;O'Brien et al 2003). Nanochannels were fabricated in glass, silicon, polyimide, PDMS and Au (Eijkel et al 2004;Hug et al 2003;Zaumseil et al 2003).…”
Section: Introductionmentioning
confidence: 99%